Stylistic Features in Pantau Coverage: A Stylistic Study and Its Relationship with Indonesian Language Learning - Utami, Pramudya Ashya Novika; Maruf, Ali Imron Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to discuss the language styles used in Pantau's coverage features. The language styles employed in the coverage are deliberately crafted to enhance readers' comprehension and engagement with news presented in feature format. The research utilizes a descriptive qualitative method, with data collection conducted through literature study techniques involving careful and thorough reading of Pantau's coverage features. Data analysis employs semiotic reading methods, including heuristic and hermeneutic readings, to uncover the meaning of the data studied. The research findings and discussions reveal: (1) feature coverage contains language styles such as sound style, word style, sentence style, discourse style, figurative language, and imagery. Journalists utilize these language styles in both narrative and dialog sections of feature coverage; (2) concerning Indonesian language learning, the study's results are relevant to phase E in the Independent Curriculum for learning news texts. This phase can be utilized by students to comprehend features or express news with appropriate language styles.